PENGEMBANGAN ALAT UKUR INTENSITAS SUARA (BISING) BERBASIS KOMPUTER - ., Sujito (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2010)
This study aims to build a sound intensity measuring instrument (noise), which is equipped with the tools perakaman recording data so that data can be processed if necessary. This research was completed with the descriptive approach, which describes the process of making the sound intensity measuring instrument (noise)-based computer. The data obtained were analyzed by correlation of the variables obtained. To calibrate the intensity of sound measured in dB and the output measure in binary form. Results from this penelititan form a sound intensity measuring instrument and a software (computer program) to record data (output devices) as well as interface with the user.Â Keywords: Measurement, Sound, Computer-Based